Increasing livestock productivity in mixed crop-livestock systems in South Asia: Proceedings of the planning workshop of regional stakeholders, ICRISAT, India, 15-17 November 1999 - Thomas, D. (International Crops Research Institute for the Semi-Arid Tropics, 1999)
The purpose of the project "Increasing livestock productivity in mixed crop-livestock systems in South Asia" is to develop a crop-livestock typology that will ultimately improve the effectiveness of technical and socio-economic interventions aimed at improving animal performance and protecting the natural resource base at farm level in South Asia. The workshop provides an overview of the project proposal, the allocation of resources for specific activities, the definition of specific milestones, a description of crop-livestock systems in the regions and the status of data available on livestock production in the four countries, viz, Bangladesh, Nepal, Sri Lanka, and Gujarat.